On show : temporary design for fairs, special events, and art exhibitions. (Berkeley, Calif. : Ginko Press, 2012)
The beauty of impermanence has many manifestations whether in the artistic, natural or spiritual realms. Each transitory piece elicits a precious response in the participant a heightened awareness of the senses occurs in order to capture impressions before it is too late. The design of exhibition and trade show stands exemplifies this temporary quality, providing intriguing displays that are at once eye catching, sophisticated and memorable. Whether controlled or interactive, the installations featured frequently make use of all surfaces from floor to ceiling to arrest one s attention and direct further explorations. Through the innovative use of lighting, multimedia displays and custom fixtures, a story is told, creating a unique experience for the visitor and a reference for future recommendations.
boek